Epidemiology Study of the Head Lice Pediculus humanus capitis Isolated among Primary School Students in Erbil city, Kurdistan Region, Iraq - S. AL-Marjan, Karwan; M.A. Abdullah , Shamall; H. Kamil, Fouad (Diyala Journal of Medicine, 2022)
Background: The association between man and the head lice is one of the oldest relationship and its history return to 10000 years ago. Blood sucking head lice belong to Kingdom Animalia, Class: Insecta, Order: Phiroptera, Family: Pediculidae, Genus: Pediculus, Species: humanus and Subspecies: capitis that’s obligate parasite on human this highly specialized to suck blood and close association with their host where completed its entire life cycle. Objective: To determine the rate of infestation by the head lice, Pediculus humanus capitis and its associated factors among primary school children in Erbil City. Patients and Methods: A case control study was conducted on the twenty two (22) randomly selected primary school in the center of Erbil city. For this purpose, a total of 1082 students (430 boys and 652 girls) were examined from first to sixth stage (age ≥6 years old) during 1st October 2020 to 31th May 2021. Personal requested information was recorded by student parents in a questionnaire form. Results: An overall prevalence of infestation of 25.5% (276/1082) was recorded in the present study. Study reveals the existence of a significant relationship age [6 and < 9 years old , 178/759 (23.5%), and ≥ 9 years old, 98/323 (30.3%), P = 0.0174], gender [girls, 215/652 (33%) and boys, 61/430 (14.2%), P < 0.001], education level of parent (educated family, 146/694 (21%) and none educated family, 130/388 (33.5%), P < 0.001], longevity of hair [ long hair, 157/473 (33.2%) and short hair 119/609 (19.5%), P < 0.001] hair washing frequency [daily washing, 243/587 (41.4%), and weekly washing 33/495 (6.7%), P < 0.001], hair combing condition [common comb user,165/499 (33%) and special comb user, 111/583 (19%), P < 0.001] and sleeping habitat [ sleeping together 222/693 (32%) and sleeping habitat alone, 54/389 (13.9%), P < 0.001]. There’s no significant existence related to density of students in classroom [ one student per table, 114/486 (23.5%) and sitting in pair, 162/596 (27.2%), P = 0.1621], hair type, smooth and wrinkle [smooth hair, 183/741 (24.7%), 93/341 (27.3), P = 0.366] and head lice infestation. Conclusion: We concluded that head lice infestation rate was varied depending on the several physio and socioeconomic factors including, age, gender, type of hair, education level of parents, frequency of hair washing, sleeping habitat and condition of hair combing. Among variables, only density of pupils in classroom, smooth and wrinkled hair show no any significant relationship with pediculosis capitis (P- value = 0.1621 and P –value = 0.366 respectively).